1981
DOI: 10.1007/bf02462445
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on the shell mineralogy ofMytilus edulis

Abstract: The shells of Mytilus edulis in the Tay estuary, Scotland, show mean aragonite contents of 55%, but in one zone the average aragonite proportion is only 45%. Comparison with data for Mytilus edulis from other regions indicates the temperature and salinity are not the only significant determinants of the aragonite/calcite ratio. Elimination of other variables suggests that sewage discharges may influence the mineralogy of the shell secreted by Mytilus edutis in the relatively nutrient-enriched areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Results clearly highlight a dependency of calcification rates on pCO 2 and [CO 3 2− ] values for both species, although oysters appeared to be far less sensitive than mussels as shown by the lower slope of the lines between either pCO 2 or [CO 3 2− ] and net calcification. This can be partly explained by their different shell mineralogy, as the shell of Crassostrea gigas is mainly composed of calcite [ Stenzel , 1963], while the shell of Mytilus edulis can contain up to 83% of aragonite [ Hubbard et al , 1981]. Tables 1 and 2 list the parameters measured during each incubation (pH and TA), computed pCO 2 and CO 3 2− concentrations, as well as the computed calcite and aragonite saturation states.…”
Section: Resultsmentioning
confidence: 99%
“…Results clearly highlight a dependency of calcification rates on pCO 2 and [CO 3 2− ] values for both species, although oysters appeared to be far less sensitive than mussels as shown by the lower slope of the lines between either pCO 2 or [CO 3 2− ] and net calcification. This can be partly explained by their different shell mineralogy, as the shell of Crassostrea gigas is mainly composed of calcite [ Stenzel , 1963], while the shell of Mytilus edulis can contain up to 83% of aragonite [ Hubbard et al , 1981]. Tables 1 and 2 list the parameters measured during each incubation (pH and TA), computed pCO 2 and CO 3 2− concentrations, as well as the computed calcite and aragonite saturation states.…”
Section: Resultsmentioning
confidence: 99%
“…Gazeau et al (2007) ascribed the observed difference in calcification under elevated CO 2 conditions to differences in shell mineralogy between the species. Adult oyster shells are mainly composed of calcite (Stenzel 1964), while adult mussel shells contain up to 83% aragonite (M. edulis; Hubbard et al 1981). Since the K* sp is larger for aragonite than for calcite, aragonite is less stable and therefore more soluble than calcite (Zeebe & Wolf-Gladrow 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Along similar lines, many invertebrates have the capacity to alter the crystalline structure of their shells. Bivalves employ different polymorphs of CaCO 3 during various developmental stages (including amorphous CaCO 3 , aragonite and calcite) and incorporate different combinations of polymorphs as a function of environmental conditions (Hubbard et al, 1981; Al-Dabbas et al, 1984;Falini et al, 1996;Weiss et al, 2002; Addadi et al, 2003). Each of these changes has the potential to influence shell integrity.…”
Section: Functional Costs Of Ocean Acidificationmentioning
confidence: 99%